A Targeted Sequencing Study of Glutamatergic Candidate Genes in Suicide Attempters with Bipolar Disorder - Gaynor, Sophia C. (Am J Med Genet B Neuropsychiatr Genet, 2016)
Suicidal behavior has been shown to have a heritable component that is partly driven by psychiatric disorders [Brent and Mann, 2005]. However, there is also an independent factor contributing to the heritability of suicidal behavior. We previously conducted a whole exome sequencing study of bipolar suicide attempters and bipolar non-attempters to assess this independent factor [Monson et al., 2016]. This whole exome study implicated glutamatergic neurotransmission in attempted suicide, as did our genome-wide association study (GWAS) of the attempted suicide phenotype [Willour et al., 2012]. In the current study, we have conducted a targeted next-generation sequencing study of the glutamatergic N-methyl-D-aspartate (NMDA) receptor, neurexin, and neuroligin gene families in 476 bipolar suicide attempters and 473 bipolar non-attempters. The goal of this study was to gather sequence information from coding and regulatory regions of these glutamatergic genes to identify variants associated with attempted suicide. We identified 186 coding variants and 4,298 regulatory variants predicted to be functional in these genes. No individual variants were overrepresented in cases or controls to a degree that was statistically significant after correction for multiple testing. Additionally, none of the gene-level results were statistically significant following correction. While this study provides no direct support for a role of the examined glutamatergic candidate genes, further sequencing in expanded gene sets and datasets will be required to ultimately determine whether genetic variation in glutamatergic signaling influences suicidal behavior.